Cholecystokinin in transient lower oesophageal sphincter relaxation due to gastric distension in humans. Issue 5 (May 1997) - Boulant, J; Mathieu, S; D'Amato, M; Abergel, A; Dapoigny, M; Bommelaer, G
Abstract : BACKGROUND AND AIMS: Transient lower oesophageal sphincter relaxations (TLOSRs) has been found to be the main mechanism of gastro-oesophageal reflux. In dogs, cholecystokinin (CCK) is involved in their occurrence. The aim was to evaluate the role of endogenous and exogenous CCK in the occurrence of TLOSRs induced by gastric distension at constant pressure in humans. METHODS: Ten healthy volunteers were studied. Lower oesophageal sphincter pressure was monitored with a sleeve device and gastric distension was performed via an intragastric bag monitored by a barostat. During distensions, saline, CCK (30 ng/kg/h) or the CCK-A receptor antagonist loxiglumide (10 mg/kg/h) was perfused in a random double blind order. RESULTS: There was no significant difference between the number of TLOSRs during the different distensions with saline; CCK increased the number of TLOSRs at a mean rate of 13.1 compared with 9.1 with saline (p < 0.001). Loxiglumide significantly decreased the number of relaxations to 5.3 versus 8.3 under paired saline infusion (p < 0.001). CONCLUSIONS: In humans, CCK-A receptor subtype is involved in the occurrence of transient lower oesophageal sphincter relaxations induced by gastric distension.